ROLE OF DILATATION AND CURETTAGE AND INTERPRETATION OF ENDOMETRIAL BIOPSY IN GYNAECOLOGICAL CASES - Abbasi, Aziz -un-Nisa; Khan, Khalid; Majid, Shamim S. (Journal of Ayub Medical College Abbottabad, 1998)
3 JO Cases of diagnostic D and C were collected randomly from Gynae unit of Lady Reading Hospital Peshawar from January 1990 to January 1991. These were cases of infertility> 49.26 %, menorrhagia 13.22 %, irregular bleeding 29.67 %, Postmenopausal bleeding 5.16 %, primary’ and secondary’ infertility 30.96 % and 18.38 % respectively. Various aspects like age, parity, marital status, clinical features and histopathological results were analysed. 6.45 % were below the age of 20 years. 63.22 % between 21 to 40 years, 25.16 % between 40-50 years and 5.16 % were above the age of 50 years. 16.45 % patients were nullipara. 15.48 % Primiparae and 37.09 % and 30.96 % were multipara and grand multipara respectively. 0.64 % patients were un-married, 84.83 % were married and 40.51 % were widows. Results of endometrial biopsies were as follows. Proliferative phase 47.74 %. secretory’ phase 35.48 %. tuberculous endometritis 1.93 %, cystic endometrial hyperplasia 8.38 %, Adenomatous hyperplasia 1.29 % and adenocarcinoma 0.96 %.